Photobiocatalytic decarboxylation for olefin synthesis. Issue 10 (22nd December 2014) - Zachos, Ioannis; Gaßmeyer, Sarah Katharina; Bauer, Daniel; Sieber, Volker; Hollmann, Frank; Kourist, Robert
Abstract : The oxidative decarboxylation of fatty acids to terminal alkenes was accomplished with high selectivity by combining a fatty acid decarboxylase OleTJE with the light-catalyzed generation of the cosubstrate hydrogen peroxide, resulting in a simple and efficient system for the light-driven cleavage of C–C bonds. Abstract : Here, we describe the combination of OleTJE with a light-driven in situ H2 O2 -generation system for the selective and quantitative conversion of fatty acids into terminal alkenes. The photobiocatalytic system shows clear advantages regarding enzyme activity and yield, resulting in a simple and efficient system for fatty acid decarboxylation.